2000
DOI: 10.1262/jrd.46.31
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Observation of Follicular and Luteal Dynamics during the Estrous Cycle in Shiba Goats.

Abstract: Abstract. Transrectal ovarian ultrasonography was performed to examine follicular and luteal dynamics during the estrous cycle in four adult female Shiba goats. Detectable follicles and the corpora lutea in both ovaries were monitored daily for 44 days using a B-mode scanner with a 7.5 MHz transrectal transducer. Blood samples were collected by jugular venipuncture at the time of ultrasonography and analyzed for estradiol-17β and progesterone by radioimmunoassay to monitor ovarian activity. Three to six follic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
32
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 20 publications
11
32
1
2
Order By: Relevance
“…The limited diet level was chosen as the most severe level not to affect clinical general condition in consideration of previous reports [9,18]. The f o l l i c u l a r d e v e l o p m e n t , o v u l a t i o n a n d development of corpora lutea were monitored daily by transrectal ultrasonography until the determination of ovarian quiescence as described previously [16]. The diameter of detectable follicles and the major axis of the corpus luteum were measured with the scanner's electronic calipers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The limited diet level was chosen as the most severe level not to affect clinical general condition in consideration of previous reports [9,18]. The f o l l i c u l a r d e v e l o p m e n t , o v u l a t i o n a n d development of corpora lutea were monitored daily by transrectal ultrasonography until the determination of ovarian quiescence as described previously [16]. The diameter of detectable follicles and the major axis of the corpus luteum were measured with the scanner's electronic calipers.…”
Section: Methodsmentioning
confidence: 99%
“…P l a s m a w a s s e p a r a t e d b y centrifugation immediately after the collection and st o red fro zen at -20 C un til t he as says for concentrations of progesterone and estradiol. Because we have reported that the ovulation occurs within 7 days after the onset of luteal regression during the normal estrous cycle in Shiba goats [16], th e a n i m a l s th a t h a d n o ov u l a ti o n fo r 1 4 consecutive days (twice normal value) after the regression of corpus luteum from the ovarian i m a g e w e r e d ia g n o se d as h av in g o v a r i an quiescence. The onset of ovarian quiescence was determined as the first day of successive daily b l e e d i n g d a t e s w h e n c o n c e n t r a ti o n s o f progesterone were lower than 1 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The early return to active follicular development in West African Sahelian goats demonstrated the ability of the ovary to resume activity early after kidding. In Shiba Goats, three to six follicles, whose diameters ranged from 1 to 7 mm, were observed throughout the cycle; a few follicles grew to more than 5 mm in diameter and most of them atrophied during the luteal phase (Orita et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…During the period between days 7 and 14 after ovulation, the corpus luteum was considered to have been fully developed, as described previously [17]. The dosage of TAK-683 was determined based on previous studies [15,16], i.e.…”
Section: Methodsmentioning
confidence: 99%